Efektivitas Program Warung Cerdas Kelompok Usaha Bersama (KUBE) di Desa Wisata Jatiluwih Kabupaten Tabanan - Rika Wiliana, Putu Dian; Winaya, I Ketut; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
The KUBE Smart Store Project in Jatiluwih Tourist Village is one of the Tabanan Regency Social Office’s plans to improve the welfare of beneficiaries of social assistance and is a representative place to accommodate and release quality products from KUBE members. In terms of developing product innovation and using social media, the implementation of the KUBE Smart Shop plan is still not the best choice. The purpose of this research is to determine the effectiveness of the KUBE smart store program in Jatiluwih tourist village. Collect data through interviews, observations and literature research. Based on the study of effectiveness theory and target performance, integration and adaptability indicators. The results show that the effectiveness of Jatiluwih Tourist Village's KUBE smart store program has been operating effectively, but needs to be optimized again, especially in terms of capital and technology updates. Keywords: Program, Effectiveness, Joint Business Group